Suicide justice: Adopting Indigenous feminist methods in settler suicidology. (January 2022) - Cardon, Kristen
White settler colonies around the world have long reported disproportionately high rates of Indigenous suicides, a consequence of the continuing violence of imperialism. This article posits a need for interdisciplinary approaches to address this crisis and therefore turns to humanist methods developed in Indigenous and feminist scholarship. I analyze texts from U.S. psychologist Edwin Shneidman to rearticulate their relationship to what I call settler suicidology. I then evoke literary critic Eve K. Sedgwick's reparative reading method to reimagine suicide prevention as suicide justice, reading the novel There There by Tommy Orange (Cheyenne and Arapaho) to advocate for distributive justice as a new approach to Indigenous suicide crises. My term suicide justice names increasing accountability between settler suicide workers and the communities they seek to serve.